2022
DOI: 10.33578/pjr.v6i4.8841
|View full text |Cite
|
Sign up to set email alerts
|

Gesit Edusex: Pengembangan Media Berbasis Google Sites Sebagai Media Pengetahuan Seks Di Kalangan Mahasiswa

Abstract: Pendidikan seks adalah pengetahuan terkait seksualitas manusia yang dapat digunakan untuk mencegah kekerasan seksual. Pendidikan seks penting diterapkan dalam kehidupan mahasiswa untuk mencegah biasnya pendidikan seks di kalangan remaja saat ini. Hal tersebut dapat diakibatkan karena rendahnya pengetahuan terhadap pendidikan seksual. Tujuan penelitian pada artikel ini adalah mengembangkan media pembelajaran Gesit Edusex, yakni media pembelajaran berbentuk e-learning yang berisi tentang pendidikan seks dari ber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Previous studies by Widayanti (2022), Nanang (2020), and Tiara (2022) indicated favorable outcomes in creating internet-based learning tools for instructing children about self-protection. The popularity of the internet among teenagers has caused a surge in the implementation of digital technology for educating children about sexual safety.…”
Section: Development Of Web-based Digital Learning Mediamentioning
confidence: 98%
“…Previous studies by Widayanti (2022), Nanang (2020), and Tiara (2022) indicated favorable outcomes in creating internet-based learning tools for instructing children about self-protection. The popularity of the internet among teenagers has caused a surge in the implementation of digital technology for educating children about sexual safety.…”
Section: Development Of Web-based Digital Learning Mediamentioning
confidence: 98%